BAITUL MAAL WA TAMWIL: DITINJAU DARI ASPEK HUKUM - Handieni Fajrianty; Nurhasanah Nurhasanah (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2019)
The purpose of this study is to analyze the implementation of the Cooperative Act Number 25/1992 and the Microfinance InstitutionAct No. 1/2013 within the Baitulmaal Wa Tamwil (BMT) in Tangerang Selatan. Unit of analysis of this study are 3 prominent BMTs in Tangerang Selatan namely: Koperasi Serba Usaha (KSU) BMT Universitas Muhammadiah Jakarta (UMJ), KSU BMT Al-Jibal and Koperasi Simpan Pinjam Pembiayaan Syariah (KSPPS) BMT Syahida UIN Jakarta. Scope of this study is limited to the subject of legal certainty that regulates the operation of BMT. In order to find the accurate summary of legal certainty from the legal standing of BMT, this study uses qualitative method with content analysis and comparative analysis approachin order to analysis the data. To describe the the finding this reseach also uses structured interview to manajer and directors from the 3 BMTs. The findings of this research are the implementions of these laws does not give legar certainty to the operation of BMT. Based on the interview to the practitioners this study finds that the aspect of customer services the BMTs do not refer to the law. They still deal to the non-member customers by delivering financing them.